Has the national fall in smoking rate in Ireland been replicated in cancer patients? a 5-year report. (20th October 2021) - Bhardwaj, N; Fox, P; Frazer, K; Lyons, A; Doherty, K; Fitzpatrick, P
Abstract: Background: Population smoking rates are falling in Ireland, however many cancer patients continue smoking post diagnosis, despite its association with poorer treatment and clinical outcomes. As part of a feasibility study of smoking cessation for cancer patients in Ireland, a review of smoking rates in cancer patients was undertaken. Methods: The Hospital Inpatient Enquiry system (HIPE), a national database which collects administrative, demographic & clinical data on discharges from public hospitals in Ireland, provided data (2014-2018) on smoking status of adult discharges with a cancer diagnosis (overall, breast, lung, cervical and head & neck (H&N). Smoking trends were compared with Healthy Ireland data (2015-2018), from a national survey for adults on health & wellbeing. Results: During 2014-18, current smoking rose for all cancers (10.5%-11.4%), cervical cancer (11%-19.8%) and initially (2014-2016) for H&N (3%-12.7%) and lung (24.7%-27.2%), which dropped to 7.6% and 24% respectively in 2018; breast was stable at 6 ± 0.6%. Rates are lower than the general population (23%-20%). During 2014-17, past smoking rates demonstrated an upward trend among all cancers and specific cancers, with the highest prevalence among lung (30.3-39%) and lowest among breast (7.3-11%); comparative general population data was 23-28%. Current smoking rates for all cancers were highest among 50-59-year-olds (14-16%), which contrasts with the general population (24-35 years at 32-28%). Current and past smoking rates for all cancers were consistently higher among males, similar to the general population. Conclusions: HIPE data is limited by duplicate episodes of care, and it is recognised that smoking documentation may be an underestimate. However, it is useful to analyse trends, as these limitations should be stable over the 5-year study period. Rates remain high; our further research will document barriers and facilitators to smoking cessation among cancer patients. Key messages: Smoking rates in cancer patients are high despite proven benefits of smoking cessation. Supportive smoking cessation services as part of routine cancer care are indicated.